2022
DOI: 10.3390/ijerph20010741
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Access and Use of Health Care Services among Settled Immigrants, Recent Immigrants, and Locals: A Comparative Analysis of a Nationally Representative Survey in Chile

Abstract: Globally, and particularly in the Latin American region, international migration continues to grow. Access and use of health care services by migrants vary according to their country of origin and residence time. We aimed to compare the access and use of health care services between international migrants (including settled migrants from Peru, Argentina, Bolivia, Ecuador; Emerging migrants from Venezuela, Dominican Republic, Colombia, Haiti; and migrants from other countries) and the Chilean population. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Based on our review, diverse efforts have been made to address migrant’s health needs in Latin America, including chronic diseases, as evidenced in Chile with the “AUGE-GES” (Explicit Health Guarantees plan) that prioritizes prevalent conditions from which migrants can be benefited regardless insurance status. These efforts conducted by the health system show progress in the region, but like other legal provisions, it should be monitored and reinforced ( 48 ). Challenges related to accessing care in migrant populations have been described, which could be exacerbated by administrative and bureaucratic barriers, discrimination within healthcare settings and lack of intercultural pertinence and competence ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our review, diverse efforts have been made to address migrant’s health needs in Latin America, including chronic diseases, as evidenced in Chile with the “AUGE-GES” (Explicit Health Guarantees plan) that prioritizes prevalent conditions from which migrants can be benefited regardless insurance status. These efforts conducted by the health system show progress in the region, but like other legal provisions, it should be monitored and reinforced ( 48 ). Challenges related to accessing care in migrant populations have been described, which could be exacerbated by administrative and bureaucratic barriers, discrimination within healthcare settings and lack of intercultural pertinence and competence ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Even in countries that promote access to healthcare for migrants, many Latin American countries show restrictions in healthcare service provision to these populations due to both policy gaps and implementation pitfalls ( 50 , 51 ). Consequently, experiencing delays and restrictions for healthcare provision might have an impact on the search for private care with out-of-pocket expenditure and the search for treatment outside the healthcare system ( 48 , 52 , 53 ). In this context, there are a few examples -like one from Colombia- in which health policies advocate for health workers training to develop intercultural competences to promote the prevention and early diagnosis of chronic diseases among migrants ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it should be further assessed if, in spite of a higher access to mental health care among women, there are undetected inequalities for women as well. For instance, migrant population in Chile has a higher proportion of health uninsurance and lower consultation in case of accident or illness (Oyarte et al, 2022 ). Previous research has shown that there is a broad mental health gap among women if socioeconomic position is considered (Jiménez-Molina et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, an individual's initial evaluation for depressive symptoms and professional diagnosis for major depression is often hindered by various factors such as limited awareness, stigma, mistrust with health service providers, and restricted access to healthcare (8, 9). Consequently, depressive symptoms usually remain undetected until turning to depressive disorder in later stages, particularly within marginalized groups, such as migrants and refugees, who typically experience health disparities in the host country (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%